ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN DITINJAU DARI SEGI MANAJEMEN MODAL KERJA, LIKUIDITAS, LEVERAGE, SIZE, DAN SALES GROWTH (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2008- - SE, M.Si, Risgiyanti; SE, M.Si, Doni Eko Mardono (STIE Muhammadiyah Pekalonga, 2015)
The research entitled âThe Analysis Factors Influencing the Firm Profitability in terms of Working Capital Management, Liquidity, Leverage, Size, and, Sales Growthâ aims to analyze the effect of receivables collection period, payables deferral period, cash conversion cycle, current ratio, debt ratio, size and sales growth on profitability of companies manufacturing consumers goods industry sector listed on the Indonesia Stock Exchange (IDX) periode 2008-2012. Research data were taken from the financial statements audit of company manufacturing consumer goods industry sector listed on BEI in 2008 until 2012. The data obtained from the IDX website and Indonesian Capital Market Directory (ICMD) 2008-2012. By using purposive sampling method, this research using 11 companies as theÂ sample. Methods of analysis used are descriptive statistics, multiple regression analysis and a classic assumption test, while to test the level of significance was used simultaneously test (test F) and partially test (t-test). Based on the analysis, simultaneous testing indicates that theÂ Â receivables collection period,Â payables deferral period, cash conversion cycle, current ratio, debt ratio, firm size, and sales growth together have significant impact on firm profitability. For partial test indicates thatÂ payables deferral period and cash conversion cycle have negative and significantÂ effect on profitability. Current ratio, size and sales growth have positive and significant effect on profitability. While the receivables collection period and the debt ratio have no impact on profitability of companies manufacturing consumer goods industry sectors listed on the Indonesia Stock Exchange. Keywords : profitability, working capital management, liquidity, debt, firm size, sales growth.